Not so Myopic Consumers - Evidence on Capitalization of Energy Technologies in a Housing Market - Oskari Harjunen; Matti Liski (Center for Economic Studies and ifo Institute (CESifo), 2014)
Policies affecting the cost of energy use provide correct incentives for technology choices only if there is a market reward for energy efficiency. We provide clean evidence for market efficiency by considering how heating technologies capitalize into house values using detailed Finnish register data on technologies in houses, transaction prices and socio-economic variables. We exploit variation in technologies that houses are locked into at construction time to identify the stand-alone value of having a cost-saving technology in the house. For the two main technologies, electric and district heating, the estimated price discount is 5-6% of the house value for electric heating, coming very close to the capitalized value of the cost differ-ential obtained from external data on energy contract prices. Technologies act as labels with clear market valuation - the results support the idea that transparent energy-efficiency classification of houses capitalize into house prices.
Keywords: D12; H23; Q42; Q50; 330; energy efficiency; energy paradox; discounting